Pengaruh Model Pembelajaran Self Organized Learning Environment (SOLE) Berbasis Scaffolding terhadap Kemampuan Berpikir Kreatif dan Hasil Belajar Geografi Siswa di SMA - Darmawan Aditama Aditama; Sri Astutik; Era Iswara Pangastuti; Fahmi Arif Kurniawan; Bejo Apriyanto (Geography Education Study Program, Universitas Kanjuruhan Malang, 2023)
Education is an important driver for human development starting from communication, information, character and nature. Relevant learning resources will make it easier for students to be able to develop knowledge in their respective fields. Based on the observations of the limitations of teachers in supporting learning, there are still many shortcomings, one of which is in terms of the learning model implemented in the classroom. Efforts to improve student thinking that is creative and prove student learning outcomes with the SOLE learning model based on Scaffolding. The research objective was to examine the effect of the Scaffolding-based SOLE learning model on creative thinking skills and geography learning outcomes in high school. This type of research is quasi-experimental. This study uses a pretest and posttest design. Based on the results of the study, it was concluded that it has a significant influence on the SOLE learning model based on scaffolding on creative thinking skills and geography learning outcomes in high school. The scores resulting from the T-test for creative thinking skills obtained sig (2-tailed) values of 0.048 and 0.047, while the values resulting from the T-test of geography learning outcomes in high school obtained sig (2-tailed) values of 0.000 and 0.000.